Behavioral Health in the District of Columbia: Assessing Need and Evaluating the Public System of Care - Gresenz, Carole Roan (Rand Health Q, 2012)
This article shares findings from a study of the public behavioral health care system in the District of Columbia, including the prevalence of mental health disorders and substance use, the organization and financing of public behavioral health services, utilization of public behavioral health services, and priorities for improvement. The authors' analyses found that prevalence of mental health conditions resembles patterns nationally, among both adults and youth. Substance use disorders are more prevalent among adults and comparatively lower for the youth population, compared to national patterns. Potentially 60 percent of adults and 72 percent of adolescents enrolled in Medicaid managed care may have unmet need for depression services. Based on claims data, 45 percent of children and 41 percent of adults enrolled in Mental Health Rehabilitation Services programs have gaps in care that exceed six months during a 12-month period. Participants in focus groups and stakeholder interviews highlighted such challenges as gaps in care and difficulties in coordination of care for particular populations and services. High-level priorities include reducing unmet need for public mental health care, tracking and coordinating care, improving the availability and accessibility of substance use treatment services, and upgrading the data infrastructure.